Pengukuran Konsumsi Energi Listrik menggunakan Sensor Current Transformer TA12-200 - Maizal Isnen; Muhammad Ficky Afrianto (LPPM Politeknik Jambi, 2019)
Increasing of electrification in Indonesia still leaves several problems, such as blackouts. This can be caused by greater demand than energy availability. Businesses that can be taken to overcome this problem is include making an arrangement on the consumer side or demand side management (DMS). By implementing control technology, an Arduino-based embedded system device has been able to measure electricity consumption. The application of the TA12-200 current sensor has been able to measure electricity power with accuracy up to 96.4% and sensor resolution for about 0.4 volts per ampere. This system is equipped with an RTC module to calculate the duration of measurement, then convert the value of power (watts) into electricity energy (kWh) as well as the electricity cost in rupiah. Displaying the cost of electricity in rupiah, in this measurement system, is considered has a potential to increase user awareness to make savings on electricity usage. This is able to reduce the electricity demand, thus the cases of blackouts can be minimized.